2017
DOI: 10.1088/1674-4527/17/5/44
|View full text |Cite
|
Sign up to set email alerts
|

Seismic diagnostics of solar-like oscillating stars

Abstract: High precision and long-lasting Kepler data enabled us to estimate stellar properties with asteroseismology as an accurate tool. We performed asteroseismic analysis on six solar-like stars observed by the Kepler mission: KIC 6064910, KIC 6766513, KIC 7107778, KIC 10079226, KIC 10147635 and KIC 12069127. The extraction of seismic information includes two parts. First, we obtained two global asteroseismic parameters, mean large separation ∆ν and frequency of maximum power ν max , with autocorrelation function an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Yu et al (2018) characterized solarlike oscillations and granulation for 16 094 oscillating red giants by using the long-cadence data of Kepler, which are helpful to lift degeneracies in deriving atmospheric parameters from LAMOST. Li et al (2017) performed asteroseismic analysis on six solar-type stars observed by Kepler with the LK project atmospheric parameters serving as constraints on stellar models. Li et al (2018) conducted an analysis for the asteroseismic binary system KIC 7107778 with a non-eclipsing unresolved companion having solar-like oscillations.…”
Section: Stellar Pulsations and Asteroseismologymentioning
confidence: 99%
“…Yu et al (2018) characterized solarlike oscillations and granulation for 16 094 oscillating red giants by using the long-cadence data of Kepler, which are helpful to lift degeneracies in deriving atmospheric parameters from LAMOST. Li et al (2017) performed asteroseismic analysis on six solar-type stars observed by Kepler with the LK project atmospheric parameters serving as constraints on stellar models. Li et al (2018) conducted an analysis for the asteroseismic binary system KIC 7107778 with a non-eclipsing unresolved companion having solar-like oscillations.…”
Section: Stellar Pulsations and Asteroseismologymentioning
confidence: 99%
“…• Recent studies of KIC 6766513 and KIC 10147635 (Li et al 2017) using the YREC included element diffusion of helium and heavy elements but not convective overshooting.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%